Analysis of Technical Indicators of the “4k” Channel in The Karaulbazar District - Hikmatov F; Abduvohitov Salohiddin Samandar O’g’li (Zien Journals, 2023)
This article provides information on the technical indicators of the 4K channel, which is located in the guard farm District of the Bukhara region. A study of the technical condition of the channel revealed deficiencies and provided a summary and suggestions for eliminating existing deficiencies and improving the technical condition.
Keywords: Channel; concrete coating; filtration immersion